2022
DOI: 10.1093/eurheartj/ehac112
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction and increased cardiovascular risk in hypospadias

Abstract: Aims Hypogonadism is associated with cardiovascular disease. However, the cardiovascular impact of hypogonadism during development is unknown. Using hypospadias as a surrogate of hypogonadism, we investigated whether hypospadias is associated with vascular dysfunction and is a risk factor for cardiovascular disease. Methods and results Our human study spanned molecular mechanistic to epidemiological investigations. Clinical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…DNAH11 variants are significantly associated with congenital heart diseases (CHDs). 41 The recent study showed that boys born with hypospadias increased cardiovascular risk, 42 indicating that DNAH11 might be important to understand the pleiotropy between CHDs and hypospadias. In brief, this study improves our understanding of genetic architecture of hypospadias, especially the genetic etiology of core genes in hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…DNAH11 variants are significantly associated with congenital heart diseases (CHDs). 41 The recent study showed that boys born with hypospadias increased cardiovascular risk, 42 indicating that DNAH11 might be important to understand the pleiotropy between CHDs and hypospadias. In brief, this study improves our understanding of genetic architecture of hypospadias, especially the genetic etiology of core genes in hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…GraphPad Prism 8.0 statistical software (Graphpad, La Jolla, CA, USA) was applied for data processing [38]. The Student's t-test and one-way analysis of variance (ANOVA) were used to analyze and calculate the significance of the difference between the different groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hypospadias is a congenital malformation affecting the external male genitalia, which can lead to hypogonadism and increase the risk of cardiovascular disease in adulthood [38]. Given these phenomena, it is of great significance to explore the pathogenesis of hypospadias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of VEGFA and NO secretion in HUVECs were measured, and angiogenic and diastolic-associated proteins were quantified using Western blot. NO is a key cell-signaling molecule that is produced by activated eNOS catalyzing L-arginine [43]. Activation of eNOS and release of NO will induce the vasodilation of vessels, and NO is necessary to maintain endothelial cell function [44].…”
Section: Discussionmentioning
confidence: 99%